Cultural Acculturation: Forms, Processes, and Communication Strategies in Multicultural Families in Central Sulawesi - Juairiah Juairiah; Sugit Zulianto; Gusman Gusman; Taqwin Taqwin; Sri Mutmainah; Ridwan Wanasi; Abdul Sjahid (Asian Journal of Social and Humanities, 2023)
Diversity in diversity, but still one, has become the founding oath of the Indonesian nation so it must be avoided from cracks, let alone riots triggered by weak cultural acculturation. This study aims to describe the forms, processes, and communication strategies of immigrant communities who are culturally acculturated with indigenous people in Central Sulawesi Province, Indonesia. With a qualitative approach, this type of research is a document study on acculturation of multicultural cultures and a study of centralized interviews with informants from ethnic groups in Central Sulawesi Province, namely Javanese, Kaili, Touna, Toli-toli, and Bugis. For this reason, the source of data is in the form of text documents as evidence of published cultural acculturation, as well as information from the interview process. Simultaneously with data collection, content analysis was carried out on verbal data presented in a descriptive-qualitative manner. The results showed that the cultural acculturation of ethnic-ethnic multicultural communities in Central Sulawesi Province took the form of social gatherings (family gatherings, clan gatherings, and cultural arts performances) with a family communication process (multilingual, namely Indonesian and regional languages, as well as media) that utilized strategies cross-promotional communication (introduction, engagement, and marriage). Thus it can be concluded that acculturation of multicultural family culture in Central Sulawesi Province can be carried out by forming a new (multicultural) family. As a demographic implication, inter-ethnic differences still exist, but the formation of new cross-ethnic families can support the unity of multicultural society so that peace and harmony among citizens in Central Sulawesi is more humane